Genetic counselling in ALS: facts, uncertainties and clinical suggestions. Issue 5 (6th July 2013) - Chiò, Adriano; Battistini, Stefania; Calvo, Andrea; Caponnetto, Claudia; Conforti, Francesca L; Corbo, Massimo; Giannini, Fabio; Mandrioli, Jessica; Mora, Gabriele; Sabatelli, Mario; ,; Ajmone, Clara; et al.
Abstract : The clinical approach to patients with amyotrophic lateral sclerosis (ALS) has been largely modified by the identification of novel genes, the detection of gene mutations in apparently sporadic patients, and the discovery of the strict genetic and clinical relation between ALS and frontotemporal dementia (FTD). As a consequence, clinicians are increasingly facing the dilemma on how to handle genetic counselling and testing both for ALS patients and their relatives. On the basis of existing literature on genetics of ALS and of other late-onset life-threatening disorders, we propose clinical suggestions to enable neurologists to provide optimal clinical and genetic counselling to patients and families. Genetic testing should be offered to ALS patients who have a first-degree or second-degree relative with ALS, FTD or both, and should be discussed with, but not offered to, all other ALS patients, with special emphasis on its major uncertainties. Presently, genetic testing should not be proposed to asymptomatic at-risk subjects, unless they request it or are enrolled in research programmes. Genetic counselling in ALS should take into account the uncertainties about the pathogenicity and penetrance of some genetic mutations; the possible presence of mutations of different genes in the same individual; the poor genotypic/phenotypic correlation in most ALS genes; and the phenotypic pleiotropy of some genes. Though psychological, social and ethical implications of genetic testing are still relatively unexplored in ALS, we recommend multidisciplinary counselling that addresses all relevant issues, including disclosure of tests results to family members and the risk for genetic discrimination.